Prevalence and distribution of ossification of the supra/interspinous ligaments in symptomatic patients with cervical ossification of the posterior longitudinal ligament of the spine: a CT-based multicenter cross-sectional study. Issue 1 (December 2016) - Mori, Kanji; Yoshii, Toshitaka; Hirai, Takashi; Iwanami, Akio; Takeuchi, Kazuhiro; Yamada, Tsuyoshi; Seki, Shoji; Tsuji, Takashi; Fujiyoshi, Kanehiro; Furukawa, Mitsuru; Nishimura, Soraya; Wada, Kanichiro; et al.
Abstract Background Supra/interspinous ligaments connect adjacent spinous processes and act as a stabilizer of the spine. As with other spinal ligaments, it can become ossified. However, few report have discussed ossification supra/interspinous ligaments (OSIL), so its epidemiology remains unknown. We therefore aimed to investigate the prevalence and distribution of OSIL in symptomatic patients with cervical ossification of the posterior longitudinal ligament (OPLL). Methods The participants of our study were symptomatic patients with cervical OPLL who were diagnosed by standard radiographs of the cervical spine. The whole spine CT data as well as clinical parameters such as age and sex were obtained from 20 institutions belong to the Japanese Multicenter Research Organization for Ossification of the Spinal Ligament (JOSL). The prevalence and distribution of OSIL and the association between OSIL and clinical parameters were reviewed. The sum of the levels involved by OPLL (OP-index) and OSIL (OSI-index) as well as the prevalence of ossification of the nuchal ligament (ONL) were also investigated. Results A total of 234 patients with a mean age of 65 years was recruited. The CT-based evidence of OSIL was noted in 68 (54 males and 14 females) patients (29%). The distribution of OSIL showed a significant thoracic preponderance. In OSIL-positive patients, single-level involvement was noted in 19 cases (28%), whereas 49 cases (72%) presented multi-level involvement. We found a significant positive correlation between the OP-index grade and OSI-index. ONL was noted at a significantly higher rate in OSIL-positive patients compared to negative patients. Conclusions The prevalence of OSIL in symptomatic patients with cervical OPLL was 29%. The distribution of OSIL showed a significant thoracic preponderance.